Doping of rare earth element: The effects in elevated physical and optical properties of ZnO - Uji Pratomo; Natasha Fransisca; Muchammad Dhuhri Adzani; Irkham Irkham; Allyn Pramudya Sulaeman; Diana Rakhmawaty Eddy; Jacob Yan Mulyana; Indah Primadona (Talanta Open)
Zinc oxide (ZnO) serves as a highly adaptable semiconductor with a crucial role in various applications because of its crystal structure compatibility and significant band gap. Fabricating ZnO nanomaterials with tailored characteristics has become a prevalent and current focus. Within this framework, the integration of rare earth metals sparks interest due to their distinctive 4f electronic configuration, providing an exceptional opportunity to manipulate ZnO's optical, luminescent, and surface properties. This article examines the impact of rare earth metal doping on ZnO's structural and optical attributes, as well as the resulting improvements in various applications. We hope this review article offers comprehensive insights to guide the reasoned design and advancement of rare earth-doped ZnO (ZnO/RE) metals for various applications.